Answer:
See Explanation
Step-by-step explanation:
Your question is incomplete, as the equations or graph or table(s) were not given.
However, I'll give a general way of solving this.
Take for instance, the equations are:
![y = \frac{4}{3}x - 1](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B4%7D%7B3%7Dx%20-%201)
![y = \frac{2}{3}x - \frac{1}{2}](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B2%7D%7B3%7Dx%20-%20%5Cfrac%7B1%7D%7B2%7D)
To do this, we start by equating both equations.
![y = y](https://tex.z-dn.net/?f=y%20%3D%20y)
i.e.
![\frac{4}{3}x - 1= \frac{2}{3}x - \frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7Dx%20-%201%3D%20%5Cfrac%7B2%7D%7B3%7Dx%20-%20%5Cfrac%7B1%7D%7B2%7D)
Collect Like Terms
![\frac{4}{3}x - \frac{2}{3}x= 1 - \frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7Dx%20-%20%5Cfrac%7B2%7D%7B3%7Dx%3D%201%20-%20%5Cfrac%7B1%7D%7B2%7D)
Take LCM
![\frac{4x- 2x}{3}= \frac{2 - 1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B4x-%202x%7D%7B3%7D%3D%20%5Cfrac%7B2%20-%201%7D%7B2%7D)
![\frac{2x}{3}= \frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%7D%7B3%7D%3D%20%5Cfrac%7B1%7D%7B2%7D)
Cross Multiply
![2x * 2 = 3 * 1](https://tex.z-dn.net/?f=2x%20%2A%202%20%3D%203%20%2A%201)
![4x = 3](https://tex.z-dn.net/?f=4x%20%3D%203)
Make x the subject
![x = \frac{3}{4}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B3%7D%7B4%7D)
Substitute 3/4 for x in ![y = \frac{4}{3}x - 1](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B4%7D%7B3%7Dx%20-%201)
![y = \frac{4}{3} * \frac{3}{4} - 1](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B4%7D%7B3%7D%20%2A%20%5Cfrac%7B3%7D%7B4%7D%20-%201)
![y = 1 - 1](https://tex.z-dn.net/?f=y%20%3D%201%20-%201)
![y = 0](https://tex.z-dn.net/?f=y%20%3D%200)
Hence:
![(x,y) = (\frac{3}{4},0)](https://tex.z-dn.net/?f=%28x%2Cy%29%20%3D%20%28%5Cfrac%7B3%7D%7B4%7D%2C0%29)
10*4230 that should do the trick for ya just multiply it and ya got answer
<span />
1/4 3/5 3/4 7/5 7/3 is the correct order well at least i think it is but i hope it helps
Answer:
Step-by-step explanation:
3^t=3^(1/5)
T=1/5
Answer:
y=5/4x + 2
Step-by-step explanation:
Ok so in the point (-4,-3) -4 is x and -3 is y. Now, since you have the slope, 5/4, you can put it into an equation. -3= 5/4(-4) + b. When you multiply 5/4 x -4 you get -3=-5 + b so then add 5 to both sides to get rid of it and you have 2=b. And your equation would be y=5/4x + 2